Poznań University of Economics Students and the Labour Market (The Results of the Survey) - Kalinowska-Sufinowicz, Baha (Studia Oeconomica Posnaniensia, 2014)
The main goal of this paper is to present, analyse and evaluate young people’s expectations regarding their first job based on the results of a survey conducted among the Poznan University of Economics students in 2013. Firstly, the considerations focused on the students’ knowledge as regards the situation on the labour market and their preparation for professional work, and then on the methods, time, place and general conditions of contracts for their first job, also in terms of wage expectations.